Hostile territory - Johnstone, William W.; Johnstone, J. A. (Johnstone, William W. Preacher & MacCallister western., 2023)
"Jamie MacCallister remembers the Alamo--especially one brave frontiersman who died fighting there. Now the fallen veteran's granddaughter needs Jamie's help. She's found a letter written by her grandfather with a map to the spot where Alamo legend Jim Bowie supposedly hid a fortune in silver and gold. Jamie never believed the story. Countless treasure hunters had scoured the area and come up empty-handed. But his friend's granddaughter is convinced it's hidden where no one has ever dared to search--deep in the heart of Comanche country... There's no way Jamie will let this nice young lady venture into such hostile territory--not without his help. But they're going to need backup. Enter Preacher: easily the toughest mountain man in the West and, luckily, Maie MacCallister's loyal friend. Together, they begin their journey at Fort Belknap, the farthest outpost of civilization--and the gateway to the barbaric Comancheria. In that deadly, untamed land the three will seek their fortune. But what they find is a cutthroat gang of outlaws, a bloodthirsty group of deserters, and a powerful tribe of Comanche warriors--who kill all trespassers on sight... "